A feasibility study on low temperature thermochemical treatments of Austenitic Stainless Steel in Fluidized Bed Furnace - Haruman, Esa; Yong, Sun; Triwiyanto, Askar; Manurung, Yupiter H. P.; Adesta, Erry Yulian Triblas (Walter de Gruyter & Co, 2011)
In this work, the feasibility of using an industrial fluidized bed furnace to perform low temperature thermochemical treatments of austenitic stainless steels has been studied, with the aim to produce expanded austenite layers with combined wear and corrosion resistance, similar to those achievable by plasma and gaseous processes. Several low temperature thermochemical treatments were studied,including nitriding, carburizing, combined nitriding carburizing (hybrid treatment), and sequential carburizing and nitriding. The results demonstrate that it is feasible to produce expanded austenite layers on the investigated austenitic stainless steel by the fluidized bed heat treatment technique, thus widening the application window for the novel low temperature processes. The results also demonstrate that the fluidized bed furnace is the most effective for performing the hybrid treatment, which involves the simultaneous incorporation of nitrogen and carbon together into the surface region of the component in nitrogen and carbon containing atmospheres. Such hybrid treatment produces a thicker and harder layer than the other three processes investigated.